(untitled) (Informatica, 2014)
We are on the verge of developing artificial intelligences that may dwarf the capabilities of human intelligence. How we will interact and thrive alongside such intelligence will be a pressing societal problem. This paper addresses the question of the intelligence of "artificial persons" (organisations of people) that already exist in our modern world. A particular issue – social exclusion from the artificial persons of top professions – is explored. The paper shows how cognitonics, using telepresence, cognitive tunnelling and an advanced dialogic framework, based on the viva voce form of the Turing test, can support society in opening up pathways to its advanced professions for all of its youngsters; and at the same time train its artificial persons to work harmoniously with the other members of society. Learning how to have meaningful social dialogue with artificial persons, may be of societal value as we prepare to live among artificial persons that employ their own artificial intelligence.